2012
DOI: 10.1088/0953-8984/24/17/176001
|View full text |Cite
|
Sign up to set email alerts
|

Realizing high magnetic moments in fcc Fe nanoparticles through atomic structure stretch

Abstract: We describe the realization of a high moment state in fcc Fe nanoparticles through a controlled change in their atomic structure. Embedding Fe nanoparticles in a Cu(1-x)Au(x) matrix causes their atomic structure to switch from bcc to fcc. Extended x-ray absorption fine structure (EXAFS) measurements show that the structure in both the matrix and the Fe nanoparticles expands as the amount of Au in the matrix is increased, with the data indicating a tetragonal stretch in the Fe nanoparticles. The samples were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
(103 reference statements)
2
20
0
Order By: Relevance
“…In general, the magnetic moment of TM atoms is maximal if they are isolated and therefore the magnetic moment in a crystal increases if the nearest-neighbour distance is increased. This can be achieved for instance by a lattice stretch of an Fe crystallite, 431 effectively turning the Fe into a high-moment strong ferromagnet. But this stretch has, of course, its limits for applications which require large saturation magnetisation, i.e., a large magnetic moment per unit volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the magnetic moment of TM atoms is maximal if they are isolated and therefore the magnetic moment in a crystal increases if the nearest-neighbour distance is increased. This can be achieved for instance by a lattice stretch of an Fe crystallite, 431 effectively turning the Fe into a high-moment strong ferromagnet. But this stretch has, of course, its limits for applications which require large saturation magnetisation, i.e., a large magnetic moment per unit volume.…”
Section: Discussionmentioning
confidence: 99%
“…425 Numerous experimental studies have confirmed those predictions for free clusters and nanogranular compounds, [426][427][428][429] and also clusters embedded in NM matrices were shown to have increased magnetic moments. 426,430,431 On the contrary, there are also reports of TM nanoparticles with reduced moment, possibly as a result of oxidation. [432][433][434][435] For RE metals, certain MLs in surface proximity were predicted to have increased moments 436 which might be harnessed in clusters.…”
Section: H a Remark On Tm And Re Clusters And Nanoparticlesmentioning
confidence: 99%
“…For example, while 2 nm diameter Fe nanoparticles embedded in Ag maintain the bulk bcc structure, 159 embedding the same particles in Cu at low volume fractions causes them to adopt the fcc structure of the matrix. 162 Thus it was possible to produce embedded fcc Fe nanoparticles and stretch their lattice constant thereby causing them to switch to the theoretically predicted high-spin state of 2.5 m B /atom. 160 The method has also been used to prepare Co nanoparticles (normally fcc) in the bcc phase by embedding them in bcc Fe matrices.…”
Section: Production Of Nanoparticle Assemblies In Solid Matrices By Cmentioning
confidence: 99%
“…160 It was found that the fcc Fe nanoparticles at low volume fraction in Cu adopt a low-moment magnetic state ($1 m B /atom) but increasing the volume fraction to above the percolation threshold ($25%) causes the nanoparticles to switch to a bcc atomic structure with the bulk Fe magnetic moment of 2.2 m B /atom. 162 In addition to fundamental research, the great flexibility of cluster deposition can be exploited to produce high-performance magnetic materials. 161 Recently it has been shown that it is even possible to control the lattice constant in embedded Fe nanoparticles by embedding them in Cu 1Àx Au x alloy matrices whose lattice constant can be varied continuously by changing the Cu:Au ratio.…”
Section: Production Of Nanoparticle Assemblies In Solid Matrices By Cmentioning
confidence: 99%
“…For example we have shown recently that the lattice parameter of f.c.c. Fe nanoparticles embedded in a Cu 1-x Au x matrix can be controlled through control of the Au-content, and hence lattice parameter, of the Cu 1-x Au x matrix [20]; this led to a high level of control over the atomic moments in the f.c.c. Fe nanoparticles, allowing optimisation to values higher than those in bulk b.c.c.…”
Section: Introductionmentioning
confidence: 99%